Dynamic interaction patterns of monolingual and bilingual infants with their parents. Issue 1 (January 2020) - GAMPE, Anja; HARTMANN, Leonie; DAUM, Moritz M.
Abstract: Bilingual children show a number of advantages in the domain of communication. The aim of the current study was to investigate whether differences in interactions are present before productive language skills emerge. For a duration of 5 minutes, 64 parents and their 14-month-old infants explored a decorated room together. The coordination of their behaviors in the modalities of action, language, and gesture was coded. The results showed no differences in interactions across different language statuses. In two additional analyses, we first compared monolinguals and bilinguals with caregivers who shared the same language and culture. Results showed the same pattern of non-difference. Second, we compared bilinguals with caregivers from different cultures. The rate and duration of coordination differed across infants with different cultural backgrounds. The findings suggest that exposure to two languages is not sufficient to explain the previously identified beneficial effects in the communicative interactions of bilingual children.